LIMINALITAS AIR: POLA PERSEBARAN PATIRTHĀN DI SISI UTARA HINGGA TENGGARA GUNUNG UNGARAN - Garin Pharmasetiawan; Agus Munandar (AMERTA, 2023)
Abstract. Water Liminality: Distribution Pattern of Patirthān on the North to Southeast of Mount Ungaran. The placement of sacred buildings such as patirthān was determined by certain concepts at the time. Patirthāns on Mount Ungaran are spread from the northern side to the southeast side of Mount Ungaran i.e. slopes, valleys, plains of Rawa Pening, and north coastal plains of Semarang. This study aims to find the factors behind the distribution pattern of the patirthāns. The stages of the research consisted of data collection, analysis, and interpretation. To achieve the research objectives, the analysis was carried out using comparative and classification methods to look for differences in sacred objects that have context with the patirthān based on placement on the mountain, the relative chronology, and the shape of the patirthāns. The results show that patirthāns on Mount Ungaran can be divided into three levels of sacredness based on the form, function, and activities carried out. The distribution on the specified aspect shows the placement of the patirthāns on Mount Ungaran has a random pattern. The concept of tirthā has caused the spread of patirthān on Mount Ungaran to have a dogmatic function. This function affected the role of patirthāns as a component of the sacred area marker as well as the reinforcement of the meru concept for Mount Ungaran. Patirthān also becomes a medium of worship of Lord Shiva, who is believed to reside in the mountain. Keywords: Mount Ungaran, Sacred Geography, Distribution Pattern, Patirthān, Tirthā   Abstrak. Penempatan suatu bangunan sering kali ditentukan oleh suatu konsep yang berkembang pada suatu masa tertentu. Patirthān di Gunung Ungaran tersebar pada bagian lereng, lembah, dataran Rawa Pening, dan dataran pantai utara Semarang. Berdasarkan orientasinya dari puncak gunung, patirthān dapat ditemui pada sisi utara hingga tenggara gunung. Oleh sebab itu, kajian ini bertujuan mencari faktor yang melatarbelakangi persebaran dari patirthān di Gunung Ungaran. Tahapan penelitian yang dilakukan meliputi pengumpulan data, analisis data, dan interpretasi. Untuk mencapai tujuan penelitian, analisis dilakukan dengan metode komparasi dan klasifikasi untuk mencari perbedaan tinggalan yang memiliki konteks dengan patirthān berdasarkan posisi penempatan di gunung, kronologi relatif, dan bentuk dari patirthān-patirthān tersebut. Berdasarkan hasil analisis, patirthān di Gunung Ungaran dapat dibagi menjadi tiga tingkatan sakralitas, yaitu berdasarkan bentuk, fungsi, dan aktivitas yang dilakukan.  Berdasarkan persebaran dari aspek yang ditentukan, penempatan patirthān di Gunung Ungaran memiliki  pola yang acak. Konsep tirthā telah menyebabkan persebaran dari patirthān di Gunung Ungaran memiliki fungsi dogmatis. Fungsi tersebut berimplikasi pada peranan patirthān sebagai komponen penanda wilayah suci sekaligus penguat dari konsep meru bagi Gunung Ungaran. Patirthān dalam hal ini juga turut menjadi media pemujaan terhadap Dewa Siwa yang diyakini bersemayam di gunung. Kata kunci:  Gunung Ungaran, Geografi Suci, Pola distribusi, Patirthān, Tirthā